Commercially speaking : teacher's book - Irvine, Mark. (Oxford University Press, 1999)
The situation. Letter layout. Peter phones Teresa. Places. Formality and informality. Travel arrangements. The shop. Good commercial letters. Getting through. At a trade fiar. A letter of enquiry. Messages...